Diversity and Equity: A Global Education Challenge - Ainscow, Mel (New Zealand Journal of Educational Studies, 2016)
This article sets out the international context for this special issue on equity and diversity. Tracing the development of the United Nations’ policy ‘Education for All’ since 1990, it notes the struggles that have gone on to ensure that this is, in fact, concerned with all children, whatever their characteristics and circumstances. This inclusive vision was recently endorsed by the Incheon Declaration, which emerged from the World Forum for Education in 2015. A groundbreaking document, it makes a commitment to address all forms of exclusion and marginalisation. In so doing, it points to the need to focus efforts on the most disadvantaged learners to ensure that no one is overlooked. Bearing this new international policy in mind, the article draws on findings from the author’s own research in order to suggest an overall agenda for change, focusing on national policies for equity and the development of inclusive school practices.